The Impact of Evidence-Based Dialogic Training of Special Education Teachers on the Creation of More Inclusive and Interactive Learning Environments - Rodríguez-Oramas, Alfonso; Alvarez, Pilar; Ramis-Salas, Mimar; Ruiz-Eugenio, Laura (Frontiers in Psychology, 2021)
In the international context of a progress towards more inclusive educational systems and practices, the role of Special Education teachers is being transformed. From an inclusive perspective, these professionals increasingly support students and their teachers in the mainstream classroom, avoiding segregation. However, Special Education teachers often struggle to reach and support all students with special needs and their teachers to provide quality inclusive education. For this reason, more research is still needed on in-service training strategies for the inclusion of students with special needs that effectively translate into evidence-based school practices that improve the education of all students. This article analyses the impact of two evidence-based dialogic training programs of Special Education teachers working in mainstream schools carried out in Mexico during the 2018-2019 school year. Through in-depth interviews with participants, it was identified how, after the training, teachers increasingly grounded their actions on scientific evidence and promoted interactive learning environments that improved the educational inclusion of their students with special needs. This training also became the venue to make evidence-based educational actions available to other students without special needs, improving the quality of education provided to all students.